Biphenotypic sinonasal sarcoma with PAX3/FOXO1 fusion - Tosun, Ilkay; Karabulut, Murat H.; Yilmaz, Ismail; Cırık, Ahmet A.; Sahin, Onur (Polish Journal of Pathology, 2023)
Biphenotypic sinonasal sarcoma (BSNS), previously known as low-grade sinonasal sarcoma, is a rare tumour of the sinonasal tract, first described in 2012. It involves both myogenic and neural differentiation and is characterized by PAX3 rearrangement. MAML3 is the most frequent fusion partner of PAX3; however, its partner remains unidentified in a subset of cases. These tumours have significant local recurrence rates but lack metastatic potential. Here, we report a case of BSNS with PAX3/FOXO1 fusion and discuss its clinicopathological features and differential diagnosis.